Modulation of the Intraseasonal Chlorophyll‐a Concentration in the Tropical Indian Ocean by the Central Indian Ocean Mode. Issue 7 (7th April 2022) - Qin, Jianhuang; Meng, Ze; Xu, Wenlong; Li, Baosheng; Cheng, Xuhua; Murtugudde, Raghu
Abstract: This study diagnoses the drivers of intraseasonal variability of mixed layer chlorophyll‐a (Chl) concentration in the tropical Indian Ocean during boreal summer (June–September) using a well‐tested coupled ocean‐ecosystem model. Results show that wind forcing is the primary source for energetic intraseasonal Chl concentration variability in the eastern Arabian Sea and western Bay of Bengal (BoB) modulated by the Central Indian Ocean (CIO) mode. The atmospheric anomalous anticyclone associated with the positive phase of CIO mode drives southeastward currents in the Arabian Sea, which transport nutrient and Chl towards the east. Simultaneously, the wind‐induced offshore currents strengthen upwelling in the western boundary of BoB, resulting in enhanced Chl in the upper ocean. Conversely, because of the formation of a barrier layer, the nutrient supply is suppressed along the equator, which causes a negative correlation between the CIO mode and Chl. This study complements the Madden‐Julian Oscillation forcing on the intraseasonal Chl concentration anomaly in the tropical Indian Ocean. Plain Language Summary: A close examination in Chlorophyll‐a (Chl) is essential for monitoring in ocean biodiversity as well as fisheries resources. Previous studies have reported Chl concentration variability in the tropical Indian Ocean on intraseasonal timescale associated with Madden‐Julian Oscillation (MJO). Our study finds that the intraseasonal variability of mixed layer Chl concentration is modulated by the Central Indian Ocean (CIO) mode during boreal summer, which precedes monsoon intraseasonal oscillation. The CIO mode‐related winds induce anomalous currents in the upper ocean of tropical Indian Ocean, and thereby lead to nutrient supply, Chl blooms and advections. As a result, the Chl concentration is enhanced in the eastern Arabian Sea and western Bay of Bengal, but reduced in the tropical Indian Ocean during the positive phase of CIO mode. Our results elicit the role of the oceanic processes related to the CIO mode in the intraseasonal variability of Chl concentration, which is distinct from the MJO. Key Points: The Central Indian Ocean mode plays an important role in the intraseasonal variability of chlorophyll‐a (Chl) concentration in the mixed layer of tropical Indian Ocean The wind‐driven southeastward currents bring nutrient and Chl to the eastern Arabian Sea and enhance upwelling and nutrient supply in the western Bay of Bengal The barrier layer suppresses the nutrient supply in the tropical Indian Ocean and decreases the Chl concentration in the upper ocean